UPAYA MENINGKATKAN UMKM DENGAN DESTINASI WISATA SENDANG MBEJI DI DESA KEMIRI, KECAMATAN KEBAKKRAMAT, KABUPATEN KARANGANYAR - Terry Suseno, Adnan; Iskandar, Dibyo; Sapariyah, Rina Ani; Triono, BRM Suryo; Novita Dewi, Septiana; Haryanto, Aris Tri (INCIDENTAL : Journal Of Community Service and Empowerment, 2022)
There is a mutual relationship between MSMEs and the development of the tourism sector because MSME activities can support the tourism sector in terms of services and products to tourists. The tourism sector can also increase business opportunities for local businessmen and the community as well as provide a place for recreation for both local and foreign communities. therefore, the development of the tourism sector and the growth of MSMEs are interrelated as their activities complement each other. The aim of PKM itself is to help develop the tourism potential in Kemiri Village and its MSMEs. In addition, we also focus on developing MSMEs around Sendang Mbeji in Kemiri Village. In this activity we have 4 stages of activity, namely 1. Survey, 2. Outreach, 3 Training, and 4 Monitoring. With the various training and mentoring programs that we have provided, we hope that MSMEs in Kemiri Village can be more advanced and can support tourism there and can boost the economy in their area. Keywords: UMKM, Tourism, Community Service.